Coeliac disease: immunogenicity studies of barley hordein and rye secalin-derived peptides - Abdul Wahab, Widya; Šuligoj, Tanja; Ellis, Julia H.; Côrtez-Real, Beatriz; Ciclitira, Paul Jonathan (Wiley-Blackwell, 2016)
Coeliac disease (CD) is an inflammatory disorder of the small intestine. It includes aberrant adaptive immunity with presentation of CD toxic gluten peptides by HLA-DQ2 or DQ8 molecules to gluten-sensitive T cells. A ω-gliadin/C-hordein peptide (QPFPQPEQPFPW) and a rye-derived secalin peptide (QPFPQPQQPIPQ) were proposed to be toxic in CD, as they yielded positive responses when assessed with peripheral blood T-cell clones derived from individuals with CD. We sought to assess the immunogenicity of the candidate peptides using gluten-sensitive T-cell lines obtained from CD small intestinal biopsies. We also sought to investigate the potential cross-reactivity of wheat gluten-sensitive T-cell lines with peptic–tryptic digested barley hordein (PTH) and rye secalin (PTS). Synthesised candidate peptides were deamidated with tissue transglutaminase (tTG). Gluten-sensitive T-cell lines were generated by culturing small intestinal biopsies from CD patients with peptic–tryptic gluten (PTG), PTH or PTS, along with autologous PBMCs for antigen presentation. The stimulation indices were determined by measuring the relative cellular proliferation via incorporation of 3H-thymidine. The majority of T-cell lines reacted to the peptides studied. There was also cross-reactivity between wheat gluten-sensitive T-cell lines and the hordein, gliadin and secalin peptides. PTH, PTS, barley hordein and rye secalin-derived CD antigen-sensitive T-cell lines showed positive stimulation with PTG. ω-gliadin/C-hordein peptide and rye-derived peptide are immunogenic to gluten-sensitive T-cell lines and potentially present in wheat, rye and barley. Additional CD toxic peptides may be shared. © 2016 The Authors. International Journal of Experimental Pathology © 2016 International Journal of Experimental Pathology